Preparation of a new low-cost substrate prepared from drinking water treatment sludge (DWTS)/bentonite/zeolite/fly ash for rapid phosphorus removal in constructed wetlands. (10th July 2020) - Gao, Jingqing; Zhao, Jie; Zhang, Jingshen; Li, Qiang; Gao, Jianlei; Cai, Ming; Zhang, Jinliang
Abstract: With the increase of tap water demand and treatment volume, the by-product of the water supply plant-drinking water treatment sludge (DWTS) is increasing, and its final disposal urgently needs to be reasonably resolved. Therefore, the reuse of DWTS can not only solve the "waste" problem but also generate favorable economic benefits. This is the first study to use DWTS to prepare a regular, industrialized and efficient DWTS composite substrate (DWTSCS) for phosphorus removal in constructed wetlands by using DWTS as the main material and bentonite, zeolite and fly ash as the additive. The optimal weight ratio of DWTSCS was determined by combining orthogonal test and mixture design experiments: cement = 22.32%, DWTS = 51.62%, bentonite = 13.03%, zeolite = 4.34%, fly ash = 8.69%. The microstructure and phase analysis were performed using SEM and XRD. The static adsorption experiments showed that the adsorption behavior of DWTSCS to phosphorus conforms to a quasi-second-order kinetic model and the adsorption process can be simulated using Langmuir and Freundlich models. The maximum adsorption capacity of phosphorus by DWTSCS was calculated as 40 mg/g, and the adsorption of phosphorus with the DWTSCS was a spontaneous exothermic process. Under acidic conditions, it was favorable for DWTSCS to adsorbed phosphorus. The concentration of adsorbed phosphorus with the DWTSCS ranged from 0.5 mg/L to 0.2 mg/L. This research provides a basis for the application of DWTSCSs in constructed wetlands. Highlights: This is the first study to prepare a constructed wetland substrate from DWTS. The removal effect of DWTSCS is better than that of traditional substrates. The phosphorus removal mechanism of DWTSCS is mainly chemical adsorption. The chemical adsorption mainly involves co-precipitation and ligand exchange. The resource utilization of DWTS was achieved.